Nikah Mut'ah dalam Perspektif Hukum Islam - Luqman, Faizal (Saree: Research in Gender Studies, 2022)
The historical existence of mut'ah marriage during the time of the Prophet Muhammad is widely acknowledged among Muslims, documented in both Sunni and Shiite sources. While Shia Islam maintains the validity of mut'ah marriage indefinitely, it has been prohibited since the era of the Caliphate in Sunni tradition. This paper aims to elucidate the concept of mut’ah marriage, free from emotional bias or sectarian influences, by examining religious texts and rational arguments. Employing a qualitative research approach, this study conducts an in-depth exploration of scholarly literature and opinions, particularly focusing on the permissibility and prohibition of mut'ah marriages. The findings underscore the Shia school of thought's consistency in affirming the perpetual validity of mut'ah marriage, as no historical or Quranic evidence nullifies its legality. Conversely, the prohibition in Sunni tradition is based on hadith, consensus, and societal concerns, particularly regarding potential harm to women and children born from mut'ah unions. This research contributes to a nuanced understanding of mut'ah marriage within Islamic jurisprudence, emphasizing the importance of textual analysis and rational inquiry in interpreting religious laws. AbstrakEksistensi historis pernikahan mut'ah pada masa Nabi Muhammad diakui secara luas di kalangan umat Islam, yang didokumentasikan dalam sumber-sumber Sunni dan Syiah. Sementara Islam Syiah mempertahankan keabsahan pernikahan mut'ah tanpa batas waktu, pernikahan mut'ah telah dilarang sejak era kekhalifahan dalam tradisi Sunni. Makalah ini bertujuan untuk menjelaskan konsep pernikahan mut'ah, bebas dari bias emosional atau pengaruh sektarian, dengan mengkaji teks-teks agama dan argumen rasional. Dengan menggunakan pendekatan penelitian kualitatif, penelitian ini melakukan eksplorasi mendalam terhadap literatur dan pendapat para ulama, khususnya yang berfokus pada kebolehan dan pelarangan pernikahan mut'ah. Temuan penelitian ini menggarisbawahi konsistensi mazhab Syiah dalam menegaskan keabsahan pernikahan mut'ah, karena tidak ada bukti historis atau Alquran yang membatalkan keabsahannya. Sebaliknya, larangan dalam tradisi Sunni didasarkan pada hadis, konsensus, dan keprihatinan masyarakat, terutama mengenai potensi bahaya bagi perempuan dan anak-anak yang lahir dari pernikahan mut'ah. Penelitian ini berkontribusi pada pemahaman yang bernuansa tentang pernikahan mut'ah dalam yurisprudensi Islam, yang menekankan pentingnya analisis tekstual dan penyelidikan rasional dalam menafsirkan hukum agama.